Conceptual Understanding of Visualizer and Verbalizer Using Multiple Representation - Fariz Setyawan; Eka Zuliana; Ruzlan Md Ali (Universitas Ahmad Dahlan, 2020)
Students’ understanding of function can be seen by their representation of symbols, words, and graphs. Students’ understanding can be determined by considering their choices in defining, giving examples, and presentations of functions from the presentation choices provided for them. This study had used three types of multiple representation which comprised of symbols, words, and graphs to describe students’ understandings of functions. In this descriptive qualitative research, the researchers had classified the subjects based on verbalizer learning style and visualizer learning style. Verbalizer and visualizer learning styles are forms of cognitive learning styles. Both the verbalizer and visualizer’s works were described based on their preferences in representing the given functions. Their works, as well as their response sin the interviews, provided opportunities for the researchers to study their emerging understanding of mathematical concepts. The verbalizer tends to connect her understanding by detail explanation of the given representation. On the other hand, the visualizer tend to connect her imagination from a picture that represents her ideas.